Pembagian Harta Bersama Akibat Perceraian menurut Hukum Islam Kajian terhadap Putusan Pengadilan Agama Yogyakarta Nomor 0297/Pdt.G/2017/PA - Azhari, Moch Azam (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
All creatures of God, including humans, pets, and other animals and plants, are encompassed by the universal divine law of marriage. This is the way that Allah has chosen for His creatures to reproduce and sustain their lives. The issue of property between each husband and wife is one of the consequences of marriage law. Article 35 of the Marriage Law regulates joint property. Marital property is also acquired as joint property. The Compilation of Islamic Law states in Article 1 letter (f) that